Videogames Consumption Habits in the Administrative Zone of ”La Delicia” and "Eugenio Espejo” in Quito 2015: Time Spent on Videogames - Rosero, Gabriel (2015)
This research analyze the consume habits of videogames in the administrative zone of ”La Delicia” and Eugenio Espejo" in Quito year 2015, making a special emphasis in the dedicate time for this activity. In order to reach this objective 809 people was interviewed and descript comparative analysis was made to develop statistics charts. During the study was proven that 74.78% of the interviewed people play videogames and a digital barrier exist for the use of this products, the males plays more than women's in this market. In general the players dedicated less than one hour for this activity and the players reduce their dedicate time as their become olders. It was also proven the need of study this market for videogames that reach the characteristics of the people who are playing in Quito in order to give a new instrument to the enterprises in order to develop this market in Ecuador.